Enhancing Nutritional and Functional Properties of Plant-Based Meatballs: A Study on Kepok Banana Flower, Brown Lentils, and Wheat Gluten - Lucia Crysanthy Soedirga; Erinne Dwi Amadea (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Interest in meat substitutes has grown in recent years as consumers seek healthier options. However, many products still face limitations, either in texture or in nutritional balance. Kepok banana flower (KBF), with its fibrous structure, has the potential to mimic meat texture, though its protein content is relatively low. Brown lentils can enhance protein content, while high-protein binders such as isolated soy protein (ISP) and wheat gluten (WG) improve texture and structural integrity. This study aimed to determine the optimum ratio of minced KBF (MKBF) to brown lentil paste (BLP) and to evaluate binder formulations for nutrient-rich plant-based meatballs. The research was conducted in two stages. First, eight MKBF:BLP ratios (100:0, 90:10, 80:20, 70:30, 60:40, 50:50, 40:60, 30:70) were tested for protein content, cooking yield, and lightness (L*), identifying 40:60 as optimal. Second, the 40:60 blend was incorporated into five binder formulations: F0 (commercial reference), F1 (0% WG + 10% ISP), F2 (15% WG + 3% ISP), F3 (20% WG + 3% ISP), and F4 (25% WG + 3% ISP). Analyses included water-holding capacity (WHC), total dietary fiber (TDF), texture profile analysis, and sensory evaluation. The 40:60 ratio yielded 10.24±0.08% protein, 105.68±2.81% cooking yield, and 47.20±0.15 L*. The F4 showed the highest WHC (52.94±9.14%) and TDF (5.99±0.06%), with a hardness of 516.51±31.62 g, chewiness of 353.28±21.66 Nmm, and springiness of 0.87±0.02 mm. Sensory analysis showed that F4 was most comparable to F0. These results suggest that a 40:60 MKBF and BLP combined with WG and ISP produces consumer-acceptable plant-based meatballs with high protein and dietary fiber.